Perbandingan Data Geologi, Paleontologi Dan Arkeologi Situs Patiayam Dan Semedo - Siswanto Siswanto; Sofwan Noerwidi (Berkala Arkeologi Sangkhakala, 2015)
Java has plenty of Pleistocene sites that have recorded the development and changes of environment, as well as human beings and their cultures since more than a million years ago. The distribution of most of those sites is around the Solo Basin and along the Bengawan Solo River. However, there are also some sites, which are physiographically solitary, namely Patiayam at the feet of Mount Muria and Semedo at the east end of a mountain range in Bogor – North Serayu Zone. This article will present the current development and comparison of geological, paleontological, and archaeological data from Patiayam and Semedo, which is very valuable because they will increase our understanding of quaternary prehistory in Java, which thus far has always been dominated by data from the sites around the Solo Basin and along the Bengawan Solo River.